Morphometrical Studies on the Gastrointestinal Tract of Rabbit (Oryctolagus cuniculus) - Verma, Abhinov; Pathak, Archana; Gupta, S. K.; Farooqui, M. M.; Prakash, Ajay (Indian Journal of Veterinary Anatomy, 2018)
Three clinically healthy adult rabbits irrespective of breed were procured from the department of microbiology for the Post-Graduate teaching. The incision was given on the ventral aspect of abdominal cavity to expose the organs of abdomen. The topography and morphology of stomach, small intestine and large intestine of GIT were recorded. The biometry of different parts of GIT was done and the data was statistically analysed (Mean±SE). The total length of gastrointestinal tract from stomach to rectum was 327.13 cm. Out of which 190.89 cm was the length of small intestine and the length of large intestine was 126.08 cm. The jejunum (150±0.58 cm) was the longest part of small intestine, followed by duodenum (20.9±7.68 cm) and ilium (17.83±6.85) respectively. The terminal 2.16 cm part of ilium was rounded sac like structure known as sacculus rotundus. The diameter of ilium was maximum (1.41±0.16) followed by jejunum (0.92±0.041) and duodenum (0.68±0.01 cm) respectively. In large intestine, the caecum was large comma shaped with 35.33±4.05 and 3.24± 0.16 cm length and diameter respectively. Vermiform appendix was well developed (length 6.83± 1.09 and diameter 0.77± 0.02 cm). Ascending colon has haustrated and spiral part followed by transverse and descending colon.